2006
DOI: 10.1148/radiol.2393050253
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis of the Knee: Association between Clinical Features and MR Imaging Findings

Abstract: Purpose:To prospectively evaluate the association between clinical features and structural abnormalities found at magnetic resonance (MR) imaging in patients with osteoarthritis (OA) of the knee. Materials and Methods:The study was approved by the institutional medical ethics review board.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
227
4
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(262 citation statements)
references
References 30 publications
20
227
4
5
Order By: Relevance
“…Subsequent studies of the association of BMLs with knee pain, all of which have been cross-sectional, have either corroborated our initial findings (6) or contradicted them (7,8). This has left uncertainty as to the relationship between BMLs and knee pain.…”
supporting
confidence: 52%
“…Subsequent studies of the association of BMLs with knee pain, all of which have been cross-sectional, have either corroborated our initial findings (6) or contradicted them (7,8). This has left uncertainty as to the relationship between BMLs and knee pain.…”
supporting
confidence: 52%
“…They suggested that BMLs were associated with knee pain [15], could be predictive of progression [16] especially if they enlarged [17] or were associated with varus or valgus angulation [16]. Later reports, however, were less clear-cut even suggesting that BMLs were not only unassociated with Western Ontario and McMaster Universities index of OA scores (WOMAC™) [18,19] and other measures of patient symptoms but also fluctuated over a period of time, resolving and/or worsening with new lesions coming and going elsewhere in the same joint [20,21]. Again, these lesions did not correlate with patient symptoms.…”
Section: So Where Does the Problem Lie?mentioning
confidence: 99%
“…1 The pain and physical dysfunction of knee OA are often associated with structural damage in the patellofemoral joint (e.g., osteophytes, joint space narrowing, and reduced cartilage volume). [2][3][4] The most common involvement site of the osteoarthritis knee is the medial tibiofemoral joint and the patellofemoral joint .Within the PFJ, the lateral compartment is more frequently affected by the OA process than the medial compartment. 5 The prevalence of OA in people aged over 55 years is 20-26% and rising, with arthritis rates expected to increase by 30% over the next 40 years 6 .In a community-based study of knee OA, in Australia the frequency of radiographic osteophytes was greater in the PFJ (65%) than in the tibiofemoral joint (TFJ) (55% ).…”
Section: Introductionmentioning
confidence: 99%